Physician experiences implementing antimicrobial stewardship rounds in pediatric hospital medicine: An exploratory, qualitative study - Megan L. McCreary; Alena Tse-Chang; Karen L. Forbes; Jessica L. Foulds (Cambridge University Press, 2021)
Abstract Objectives: An antimicrobial stewardship intervention was implemented for pediatric medicine units using an in-person rounds-based approach to provide stewardship recommendations and education from an antimicrobial stewardship physician and antimicrobial stewardship pharmacist. Design, Setting, Participants, and Methods: In this exploratory qualitative study, purposeful sampling was used to recruit participants for individual interviews at a tertiary- and quaternary-care referral center. Pediatricians and residents who attended ≥1 stewardship round were included. A semistructured interview guide was created focusing on perceptions of antimicrobial stewardship, personal experiences at stewardship rounds, and perceived impacts on patient care. Using a constant comparative analysis approach, codes were developed and collapsed into themes. Results: Overall, 8 pediatricians and 10 residents completed interviews. Qualitative analysis yielded 3 themes: insights into clinical reasoning, opportunity for growth and learning, and establishing and exploring professional relationships. The handshake-rounds approach encouraged participants to critically evaluate antimicrobial choices and to engage in discussion with the antimicrobial stewardship team. Participants felt validated at stewardship rounds and gained confidence prescribing antimicrobials. Face-to-face interaction reduced reluctance for some participants to consult infectious disease (ID) service; however, others worried that physicians may avoid ID consultation because of stewardship rounds. Conclusions: Participants found stewardship rounds to be an effective strategy for education and development of clinical reasoning skills for optimal antimicrobial prescribing-choosing wisely or choosing rightly. The effects of stewardship rounds on timing and frequency of ID consultation are interesting. Further research into important patient outcomes and consultation practices are needed locally, but our experiences may help others to reflect on the power of conversation and relationships in antimicrobial stewardship.